Integrating Spatial Utilization and Sustainability Indicators for Residential Area Planning in Kediri Regency - Rusdiyanto, Edi; Munawir, Abdillah (ASTONJADRO, 2026)
The aim of this study is to analyze the current condition of land use within the context of spatial utilization in Kediri Regency, as well as to formulate policy directions for land management through a sustainable land-use change transition matrix analysis. The analytical method employed in this study involves spatial-temporal interpretation using a Geographic Information System (GIS), utilizing Landsat-7 ETM, Landsat-8 OLI imagery, and Google Earth data, combined with a mixed-method approach. The results of the spatial analysis indicate that forest land has experienced a consistent decline over time. In 2008, the forest area was 5,363 hectares; in 2013, it decreased to 5,241 hectares; in 2018, it further declined to 5,035 hectares; and by 2023, it was recorded at 4,906 hectares. In contrast, built-up land has shown a steady increase, reflecting rising urbanization in Kediri Regency and indicating growing environmental pressure due to forest reduction. In 2008, the built-up area covered 25,698 hectares; in 2013, it increased to 26,762 hectares; in 2018, it rose again to 27,955 hectares; and by 2023, it significantly expanded to 30,749 hectares. The dynamics of land-use change in Kediri Regency during the 2008–2023 period reflect a significant transformation from an agrarian character toward an increasingly urbanized area. Spatial analysis highlights the rapid expansion of built-up land as the dominant phenomenon, driven by population growth, urbanization, and regional economic development. Therefore, sustainable spatial planning policies are needed through the integration of spatial and temporal data, control of land-use conversion, and adaptive policy-making to maintain a balance between economic development, environmental sustainability, and long term societal well being. 1.854 The purpose of this study is to analyze the actual condition of land use in the context of spatial utilization in Kediri Regency and to formulate land management policy directions using a transition matrix analysis of sustainable land use. The analytical method used in this study is spatial-temporal interpretation of Geographic Information System (GIS) images using Landsat-7ETM, Landsat-8OLI, and Google Earth data, along with mixed-method analysis. The spatial analysis results indicate that forest land use has decreased over time. In 2008, forest area was 5,363 ha, in 2013 it was 5,241 ha, in 2018 it decreased again to 5,035 ha, and in 2023 the forest area was recorded at 4,906 ha. The increase in built-up land indicates increasing urbanization in Kediri Regency, while the decrease in forest area indicates environmental pressure. In 2008, the built-up area was 25,698 ha. In 2013, this figure increased to 26,762 ha. In 2018, this figure rose again to 27,955 ha. In 2023, this figure significantly increased to 30,749 ha. The dynamics of land use change in Kediri Regency during the 2008–2023 period reflect a significant regional transformation from an agrarian to an increasingly urbanized area. Spatial analysis indicates a rapid increase in built-up area, which has become a dominant phenomenon, in line with population growth, urbanization, and regional economic development. Sustainable spatial management policies are needed through the integration of spatial and temporal data, control of land conversion, and adaptive policies to maintain a balance between economic development, environmental sustainability, and long-term community welfare.